IL-18-Mediated SLC7A5 Overexpression Enhances Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells via the c-MYC Pathway - Ni, Feifei; Zhang, Tao; Xiao, Wanan; Dong, Hong; Gao, Jian; Liu, YaFeng; Li, Jianjun (Frontiers in Cell and Developmental Biology, 2021)
Abstract Objective: To investigate the role of IL-18 in the regulation of osteogenic differentiation in human bone marrow mesenchymal stem cells (hBMSCs). Methods: To assess whether IL-18 affects the osteogenic differentiation of hBMSCs through the c-MYC/SLC7A5 axis, IL-18 dose-response and time-course experiments were performed to evaluate its impact on osteogenic differentiation. To confirm osteogenic differentiation, alizarin red staining、calcium measurement were performed. RT-qPCR and western blotting were used to determine the expression levels of bone-specific markers ALP, RUNX2, and BMP2, as well as those of SLC7A5 and c-MYC. Furthermore, SLC7A5 and c-MYC expression was evaluated via immunofluorescence. To elucidate the roles of SLC7A5 and c-MYC in osteoblast differentiation, cells were transfected with SLC7A5 or c-MYC siRNAs, or treated with the SLC7A5-specific inhibitor JPH203 and c-MYC-specific inhibitor 10058-F4, and the expression of SLC7A5, c-MYC, and bone-specific markers ALP, RUNX2, and BMP2 was assessed. Results: Our results demonstrated that IL-18 increased calcium deposition in hBMSCs, and upregulated the expression of SLC7A5, c-MYC, ALP, RUNX2, and BMP2. Silencing of SLC7A5 or c-MYC using siRNA reduced the expression of ALP, RUNX2, and BMP2, while IL-18 treatment partially reversed the inhibitory effect of siRNA. Similar results were obtained by treating hBMSCs with SLC7A5 and c-MYC specific inhibitors, leading to significant reduction of the osteogenesis effect of IL-18 on hBMSCs. Conclusion: In conclusion, our results indicate that IL-18 promotes the osteogenic differentiation of hBMSCs via the SLC7A5/c-MYC pathway and, therefore, may play an important role in fracture healing. These findings will provide new treatment strategies for delayed fracture healing after splenectomy.